Advances in single-atom catalysts for lignin conversion - Halilu, Ahmed; Umar, Ahmad Abulfathi; Balarabe, Yahaya Umar; Haniffa, Mhd. Abd. Cader Mhd.; Munawar, Khadija; Sunku, Kiran; Sudarsanam, Putla (Advanced Heterogeneous Catalysts Volume 2: Applications at the Single-Atom Scale, 2020)
Single-atom catalysts (SACs) have drawn significant attention as promising surfaces for promoting observable reaction processes. As a guideline, SACs should have the proper nanoscale dimensionality to influence their effective and efficient performance, especially during lignin conversion to platform chemicals and other useful products. The development of SACs for functional applications still has many difficulties, such as harnessing and improving low-coordinated metal atoms to have controlled and observable activities per metal atom. Consequently, the need arises to ensure a decrease in the size of the metal particles and their uniform dispersion or coordination on a suitable support material. This has been an industrial target for a long time in the field of catalysis. Supported metal-based catalysts are not dimensionally uniform, thereby reducing their metal-atom efficiency and frequently leading to undesired side reactions that are sometimes difficult to observe. This makes the identification of the active sites responsible for the reaction of interest very difficult or even impossible. To ameliorate this challenge, the ultimate small-size limit for a metal particle is the SAC, which contains isolated metal atoms singly dispersed on any suitable support materials. It is expected that SACs should maximize the metal-atom efficiency with respect to the application, which is particularly significant for supported metal catalysts. Moreover, through uniform single-atom dispersion, SACs offer a great opportunity for achieving high activity and tuning selectivity to the desired product. This chapter provides a comprehensive overview of recent advances in using SACs for the conversion of lignin or lignin model compounds. The different support materials used for SACs, such as zeolites, metal oxides, and carbonaceous and siliceous materials, are discussed. This contribution also covers the catalytic reactions of lignin with an emphasis on cleaving its specific linkages, along with a systematic evaluation of SACs used in the relevant processes. The chapter also addressed key parameters essential for tailoring the particle size and acid–base and redox properties of the SACs used in lignin conversion. Special attention is paid to understanding the role of synthesis conditions in tailoring the size of SACs. It is expected that this contribution will provide future directions for practical SAC development and implementation in lignin conversion.